Expert hearings in mini-publics: How does the field of expertise influence deliberation and its outcomes? - Leino Mikko; Kulha Katariina; Setälä Maija; Ylisalo Juha (Springer, 2022)
One of key goals of deliberative mini-publics is to counteract expert domination in policymaking. Mini-publics can be expected to democratize expertise by providing citizens with good opportunities for weighing expert information. Yet, there are concerns about undue influence of experts even within mini-publics. We test these expectations by analysing data from an online mini-public organized in Finland in March 2021. The topic of deliberation was measures taken to contain the COVID-19 pandemic. We examine whether experts’ field of specialization and the order of expert hearings had an impact on how participants’ views developed. We find that neither the field of expertise nor the order of hearings had systematic effects on participants’ perceptions on containment measures. The results suggest that interactive modes of expert hearings in mini-publics seem not to be prone to domination by experts.